A meta-analysis for comparison of partial nephrectomy vs. radical nephrectomy in patients with pT3a renal cell carcinoma - Liu, Hui (Transl Androl Urol, 2021)
BACKGROUND: Kidney cancer is the most common malignant tumor of the kidney in adults. However, in terms of the treatment for pT3a renal cell carcinoma (RCC), whether partial nephrectomy (PN) can be selected is still controversial. This study was conducted to compare the efficacy of PN and radical nephrectomy (RN) in treatment for patients with pT3a RCC. METHODS: The relative English databases including PubMed and EMBASE were searched for studies comparing PN and RN for pT3a RCC between 2010 and 2020. Stata 13.0 software was used to compare the cancer-specific survival (CSS), overall survival (OS), cancer-specific mortality (CSM), relapse-free survival (RFS), complications and positive surgical margin. RESULTS: Nine articles were included with a total of 3,391 patients, of whom 2,113 received RN and 1,278 received PN. The results showed that there is no statistical difference in CSS, OS, CSM, RFS, complications and positive surgical margin between RN and PN. No heterogeneity was shown in study. CONCLUSIONS: There were no differences in the CSS, OS, CSM, RFS, complications and positive surgical margin of the patients in RN and PN group. For pT3a RCC, RN did not provide a better survival benefit compared to PN. Considering PN can suppress the progression of tumor and reduce the risk of postoperative chronic renal insufficiency, we found PN is a good choice for pT3a RCC. However, further large-sample, studies are still needed in future.